Time for a Paradigm Shift in Animal Nutrition Metabolic Pathway: Dietary Inclusion of Organic Acids on the Production Parameters, Nutrient Digestibility, and Meat Quality Traits of Swine and Broilers - Dhanushka Rathnayake; Hong Seok Mun; Muhammad Ammar Dilawar; Kwang Soo Baek; Chul Ju Yang (Life, 2021)
Because the application of antibiotic growth promoters (AGP) causes accelerated adverse effects on the animal diet, the scientific community has taken progressive steps to enhance sustainable animal productivity without using AGP in animal nutrition. Organic acids (OAs) are non-antibiotic feed additives and a promising feeding strategy in the swine and broiler industry. Mechanistically, OAs improve productivity through multiple and diverse pathways in: (a) reduction of pathogenic bacteria in the gastro-intestinal tract (GIT) by reducing the gut pH; (b) boosting the digestibility of nutrients by facilitating digestive enzyme secretion and increasing feed retention time in the gut system; and (c) having a positive impact and preventing meat quality deterioration without leaving any chemical residues. Recent studies have reported the effectiveness of using encapsulated OAs and synergistic mechanisms of OAs combinations in swine and broiler productivity. On the other hand, the synergistic mechanisms of OAs and the optimal combination of OAs in the animal diet are not completely understood, and further intensive scientific explorations are needed. Moreover, the ultimate production parameters are not similar owing to the type of OAs, concentration level, growth phase, health status of animals, hygienic standards, and environmental factors. Thus, those factors need to be considered before implementing OAs in feeding practices. In conclusion, the current review evaluates the basics of OAs, mode of action, novel strategies to enhance utilization, influence on growth performances, nutrient digestibility, and meat quality traits of swine and broilers and their potential concerns regarding utilization.